Influence of Acute and Chronic High-Intensity Intermittent Aerobic Plus Strength Exercise on BDNF, Lipid and Autonomic Parameters - Figueiredo, Caique [UNESP]; Antunes, Barbara M. [UNESP]; Giacon, Thais R. [UNESP]; Vanderlei, Luiz C. M. [UNESP]; Campos, Eduardo Z.; Peres, Fernando P.; Clark, Nicolas W.; Panissa, Valeria L. G.; Lira, Fabio S. [UNESP] (Journal Sports Science & Medicine, 2019)
The purpose of the present study is two-fold. First, we evaluated whether 8-weeks of combined training (high-intensity intermittent plus strength training) may change brain derived neurotropic factor (BDNF) and lipid parameters (triacylglycerol, HDL-c and non-HDL) in a fasted state. Second, we investigated the effect of an acute session of high-intensity intermittent exercise followed by strength training on systemic BDNF and lipid parameters pre- and post 8-weeks of training. Twenty-one healthy and physically active men were divided into two groups: high-intensity intermittent exercise combined with strength training (HSG; n = 11) and control (CG; n = 10). The HSG exercised for one minute at 100% of speedVO(2)max (sVO(2)max) interspersed with one minute of passive recovery followed by strength training (8 exercises with 8-12 repetition maximum loads) for 8-weeks. Heart rate variability, blood pressure, lipid profile, and BDNF concentrations were measured in the fasted state pre- and post-exercise and before and after the 8-week training period. After 8-weeks of exercise training, there was an increase in spectral high frequency component (ms(2)) and RR interval (p < 0.05), a decreased spectral low frequency component (nu) and heart rate values (p < 0.05), an increase in HDL-c (p < 0.001), and lower BDNF concentrations (p < 0.001). These results suggest that 8-weeks of high-intensity intermittent exercise combined with strength exercise is an effective protective cardio-metabolic strategy capable of increasing HDL-c and BDNF concentrations after an acute exercise session. In the long-term, the modulation on BDNF and HDL-c concentrations may be a determining factor for protection against neurological and cardiovascular diseases.
Keywords: HIIT; combined exercise; cholesterol; autonomic modulation; heart rate variability; health